Work Systems in A Metal Casting Company Using MEAD Approach - Ma'ruf, Farid; Mualief, Rafiq Fajar; Adiyanto, Okka (Institute of Research and Community Outreach - Petra Christian University, 2025)
Metal casting MSMEs in Indonesia often experience production inefficiencies, excessive workload, and inadequate occupational health and safety measures, resulting in reduced productivity and high worker fatigue. This study addresses these challenges by employing a macro-ergonomic framework to analyze and redesign work systems, specifically focusing on integrating cardiovascular workload (%CVL) analysis to quantify physiological strain, an approach rarely applied in small-scale industrial settings. The research was conducted at a representative metal casting MSME using the ten-step Macro-Ergonomic Analysis and Design (MEAD) method. Data collection involved direct field observations, organizational assessments, worker interviews, and physiological monitoring using wearable pulse sensors. Workload was evaluated using %CVL and energy expenditure calculations, while noise levels were measured using a sound level meter. Initial findings revealed that the average %CVL among workers reached 38.99%, categorized as “needs improvement,” with notable issues including unsafe working conditions, excessive overtime, and noise exposure exceeding 95 dB. To mitigate these issues, interventions were designed, including developing standard operating procedures (SOPs) for personal protective equipment, improved supervisory practices, and an additional 10-minute work break based on rest time calculations. Post-intervention measurements showed a reduction in average %CVL to 23.35%, bringing most workers below the fatigue threshold of 30%, alongside reported improvements in safety awareness and work satisfaction. The results demonstrate that integrating %CVL-based workload analysis within a macro-ergonomic framework provides a practical and effective solution for enhancing occupational health and productivity in labor-intensive MSMEs. This approach offers a scalable model for policymakers and industry practitioners to address systemic ergonomic deficiencies in similar informal industrial sectors.